Debt Sustainability Analysis in Reformed EU Fiscal Rules: The Effect of Fiscal Consolidation on Growth and Public Debt Ratios - Philipp Heimberger; Lennard Welslau; Bernhard Schütz; Sebastian Gechert; Dario Guarascio; Francesco Zezza (Intereconomics, 2024)
Debt Sustainability Analysis (DSA) relies on macroeconomic and fiscal policy assumptions; it plays an essential role in providing an anchor for bilateral negotiations and surveillance in the context of reformed EU fiscal rules. While the European Commission assumes a constant short-run fiscal multiplier of 0.75, the literature highlights that there is no single fiscal multiplier for all countries and all times. Furthermore, the European Commission's DSA framework assumes a fast dissipation of the output effect of fiscal adjustment, and that fiscal consolidation efforts by trading partners do not spill over into domestic economic activity. This article presents DSA simulations that relax the official assumptions by focusing on the four largest euro area economies: Germany, France, Italy and Spain. The results suggest that the debt sustainability framework in reformed EU fiscal rules is sensitive to changes in assumptions and may underestimate the negative growth effects of fiscal adjustment. Hence, public debt ratios may turn out higher than expected.
Keywords: E62; E63; O47; 330